Frequency, Pattern and Management of Acute Abdomen in Dengue Fever in Karachi, Pakistan - Muhammad Shamim (Asian Journal of Surgery, 2010)
This study aimed to determine the frequency, pattern and management of acute abdomen in patients with dengue fever. Methods: This descriptive case series is a prospective analysis of acute abdomen in dengue fever that was performed at three secondary care hospitals in Karachi, Pakistan from June 1, 2005 to December 31, 2008. The inclusion criterion was all patients with confirmed diagnosis of dengue fever. Patients with incomplete laboratory, ultrasound or histopathology data were excluded. Results: Among 357 patients with dengue fever, 43 (12.04%) had acute abdomen. There were 15 men and 28 women, with a median age of 29 years. These included 26 cases of acute cholecystitis, 7 cases of acute appendicitis, 7 cases of nonspecific peritonitis, and 3 cases of acute pancreatitis. Dengue hemorrhagic fever/shock syndrome was found in acute pancreatitis, and two of these patients died. Emergency surgery was required in eight patients (5 appendectomy and 3 open cholecystectomy). Substantial transfusion of blood and its components was required in eight patients who underwent emergency surgery. Conclusion: Early diagnosis and prompt conservative management of dengue acute abdomen is necessary to avoid mortality and emergency surgery-related morbidity. However, if needed, surgery can be performed with acceptable morbidity.